Hubungan antara Dukungan Orang Tua dengan Motivasi Belajar Piano pada Siswa Kelas 5 SD di Alunan Melodi Indonesia - Shijistaniah; Rahmah Hastuti (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to determine the relationship between parental support and motivation to learn piano in fifth-grade elementary school students at Alunan Melodi Indonesia (AMI). The background of this study is based on the phenomenon of declining motivation in children in participating in music lessons, particularly piano lessons, and the important role of support from their immediate environment, especially parents, in supporting children's learning process. The method used in this study was a quantitative correlational survey approach. Participants consisted of 110 fifth-grade elementary school students who had been taking piano lessons for six months. The instruments used were the Motivation for Learning Music Questionnaire (MLMQ) and the Parental Support Scale adapted from Sarafino (2002). The results of the data analysis showed no relationship between parental support and children's motivation to learn piano, particularly in piano lessons at AMI. This study suggests that developing children's motivation to learn music requires a more comprehensive approach, involving various factors in addition to parental support.